Fabrication and Characterization of Silane-Functionalized Na-Bentonite Polysulfone/Polyethylenimine Nanocomposite Membranes for Dye Removal - Saki, Seda; Senol-Arslan, Dilek; Uzal, Nigmet (Wiley, 2020)
In this study, tetraethoxysilane (TEOS)-functionalized Na-bentonite incorporated into polysulfone/polyethylenimine (PSF/PEI) membranes were fabricated by phase inversion method for the efficient removal of methylene blue dye. For the preparation of PSF/PEI nanocomposite membranes, silane-functionalized Na-bentonite and pure Na-bentonite were used at three different concentrations (0.5, 1, and 2 wt%). The prepared membranes were characterized by Fourier transform infrared spectroscopy, scanning electron microscopy, atomic force microscopy, porosity, hydrophilicity, and water permeability measurements. Antifouling behaviors and methylene blue dye rejections of the PSF/PEI nanocomposite membranes were also tested. The obtained results showed that the addition of pure Na-bentonite and silane-functionalized Na-bentonite both increased the water permeability of the membranes. The PSF/PEI membrane containing 2 wt% silane-functionalized Na-bentonite showed the highest water flux of 105 L m(-2) h(-1), while the lowest water flux of 1.2 L m(-2) h(-1) was recorded for pure PSF membrane. Filtration results demonstrated that the antifouling capacity was significantly increased due to the negatively charged surface of the newly generated silane-functionalized Na-bentonite PSF/PEI membranes. In summary, TEOS-functionalized Na-bentonite can be used to fabricate PSF/PEI nanocomposite membranes with effective filtration ability, antifouling capacity with lower decay ratio, higher flux recovery ratio, and 99% methylene blue dye removal performance.
Uzal, Nigmet/0000-0002-0912-3459;
Keywords: Clay; Coatings; Membranes